Credit guarantee institutions and SME finance - Leone, Paola; Vento, Gianfranco A. (Palgrave Macmillan studies in banking and financial institutions, 2012)
This book analyses and confronts the functioning of guarantee systems for SMEs in countries where these schemes had an important development. The book also highlights how the current financial crisis is modifying the guarantees schemes, through policy maker interventions.